Differential effects of corruption on export margins: insights from firm-level data of selected South Asian economies - Luqman, Muhammad (Crime, law and social change, 2025)
This research delves into the impact of corruption on both the extensive and intensive margins of exports in selected South Asian countries. To achieve this goal, we adopt a two-phase analytical approach. Firstly, we establish a theoretical framework linking corruption to extensive and intensive margins of exports. Secondly, we conduct an empirical analysis, employing the Probit, fractional probit, and two-stage fractional response models to investigate the link between corruption and export margins. Our empirical examination yields noteworthy findings. On the one hand, our estimates reveal that within a subset of South Asian economies, corruption reduces the likelihood of new firms entering the export market, thereby diminishing the extensive margin of exports as corruption levels rise. Conversely, our research finds that as corruption increases, the intensive margin of export, or the export volume of incumbent firms, tends to expand. Furthermore, our study highlights that pervasive corruption in the South Asian economies substantially hinders inter-firm reallocation in favour of the most productive firms.